Introduction: The state and historic buildings: preserving 'the national past'†. Issue 1 (28th December 2017) - Thatcher, Mark
Abstract: Historic buildings are important in nationalism through their roles in building and reinforcing national identity. As part of the expanding 'heritage industry', they are also of growing economic and political importance. Despite their physical existence, historic buildings are 'created' – they must be constructed as 'historic' through processes of choice and the attachment of significance. The state can perform these functions through policies that define and select buildings for protection, by ownership and funding, and by its uses of buildings for nationalistic purposes. Yet state actors can have good reasons – nationalistic and economic – to destroy or fail to preserve historic buildings. The paper examines why, when and how state actors pursue policies to protect historic buildings. It offers arguments about patterns of state action that part of state strategies to promote national identity and cultural nationalism.